In vitro growth of nine edible ectomycorrhizal fungi under a range of pH conditions (Bioagro, 2023)
Ectomycorrhizal fungi are considered to play an essential role in the development of forest ecosystems and can protect plant against pathogenic infections. Among other factors, soil pH may affect the successful inoculation of forest seedlings in nurseries. The effect of pH on the growth rate of strains of nine species of edible ectomycorrhizal (ECM) fungi was evaluated in vitro. In the experiments, Boletus edulis, B. aereus, B. pinophilus, B. fragrans, Amanita rubescens, Xerocomus ferrugineus, Lactarius deliciosus, Lactarius sanguifluus and Suillus luteus were grown in Petri dishes containing modified Melin Norkrans medium and adjusted at seven different pH levels. Colony area was measured at 7-day intervals for 8 weeks. Final fungal biomass and residual pH of the medium at 8th week were also measured. The optimum pH levels and pH tolerance ranges for the tested ECM fungal species are presented and discussed in the text. The results showed that the greatest growth in vitro was produced by A. rubescens and S. luteus at high pH levels (between 6.5-8.5), and by X. ferrugineus  at low pH (3.5-6.5). Almost all the strains acidified the medium where they were grown after eight incubation weeks.
Keywords: Forest ecosystems; forest seedlings; fungus biomass; incubation; nurseries